Quantum tunnelling in condensed media - Kagan, IU; Leggett, A. J. (Anthony J.) (Modern problems in condensed matter sciences, 1992)
The essays in this book deal with of the problem of quantum tunnelling and related behavior of a microscopic or macroscopic system, which interacts strongly with an "environment"--This being some form of condensed matter. The "system" in question need not be physically distinct from its environment, but could, for example, be one particular degree of freedom on which attention is focussed, as in the case of the Josephson junction studied in several of the papers. This general problem has been studied in many hundreds, if not thousands, of articles in the literature, in contexts as diverse as biophysics and quantum cosmology. The editors have grouped together papers which are representative of the main trends in this area in the last fifteen years or so and sufficiently related in general spirit and terminology that common themes can be discerned. The contributions are primarily theoretical, but the comparison with experiment is discussed wherever possible